P4_7 Santa’s Jet - Rowe, Ryan; Byworth, Kayleigh; Garner, James; Lawrence-Morgan, Dennis (Physics Special Topics, 2022)
In the movie Elf Santa replaces the waning Christmas spirit with a jet engine. We have calculated the speed required to allow Santa’s sleigh filled with presents to fly. This speed is 5500(±1700)ms−1 . This would require a thrust produced by the engine of 3.8(±2.2) × 107N.